Aura 2.0: The Technoscientific Return of Art's Religious Value. (25th February 2018) - Morelli, Michael
Abstract : In 1936 Walter Benjamin observed the 'fading of [art's] aura' as it underwent mechanical reproduction. According to Benjamin, technological advances had initiated a shift in art as a medium of 'cultic value' to art as a medium of 'display value' (Benjamin 2008, 9, 12). Eighty years later, do his observations retain their validity in a world on the brink of discovering the singularity and changing the genetic makeup of humanity, or, is art's aura beginning to burn brightly again with the joining of science, art, and liturgy in operating room theatres, mythical labs, and magical tech companies which produce chimeras, clones, cyborgs, transhumans, and intelligent robots—all which inspire religious awe? Theorist Paul Virilio ask a similar question: 'After all great periods of art, after the great schools such as the classical and baroque, after contemporary expressionism, are we not now heading for that great transgenic art in which every pharmacy, every laboratory will launch its own "lifestyles, " its own transhuman fashions?' (Virilio 2003, 61). Virilio does not seem to suggest that this new school of art produces any cultic value or authentic aura, but much of his observations about this transgenic art warrant exploration in this regard. For that reason, this paper explores the return of art's aura in the paradigm of techno-science, and in the process, develop an ethic that respond to this new art's aesthetics and its curious liturgies.